Effects of the degree of surface modification on the rheological responses of precipitated silica suspensions in benzyl alcohol. Issue 5 (4th May 2017) - Hayashi, Honami; Kawaguchi, Masami
ABSTRACT: Two types of precipitated silica powders modified by poly (dimethylsiloxane) (PDMS) were suspended in benzyl alcohol and their rheological properties were investigated as a function of silica volume fraction, φ. The suspensions were classified into sol, pre-gel, and gel states based on the increase in φ. An increase in the degree of surface modification by PDMS caused gelation at higher φ. Plots of apparent shear viscosity against shear rate in the sol and pre-gel states of highly modified silica suspensions showed weak shear thickening behavior, while the same plots for silica suspensions with a low modification level exhibited shear thinning behavior. The dynamic moduli of hydrophobic suspensions in the pre-gel and gel states were dependent on the surface modification: the storage modulus G′ was larger than the loss modulus G″ in the linear region and these moduli increased with increasing φ, irrespective of the silica powder. The linear region of the φ range for the precipitated silica suspensions was wider than that for the fumed silica powders modified by PDMS suspended in benzyl alcohol, while the G′ value in the linear region for the precipitated silica suspensions was less than those for the fumed silica suspensions. GRAPHICAL ABSTRACT: